"When the overseas provinces are called by the Constitution" (About the constitutional status of Cuba, Puerto Rico, and the Philippines, 1837-1898). - Solla Sastre, María Julia (Journal of Iberian & Latin American Studies, 2023)
This article discusses the relationship between constitution and colonies in Spain. Since 1837, Cuba, Puerto Rico and the Philippines were expressly excluded from the formal constitutions of the metropolis. Differently to the type of constitutionalism from which they were expelled, the colonies, however, seemed to retain a real and material constitution, defined by geographers with geographic criteria, which ultimately served to uphold the whole political discourse concerning the particularities of nations overseas as well as to justify, in constitutional terms, their exclusion from the series of Spanish constitutions until the final collapse of their colonial regime in 1898.